1984
DOI: 10.4319/lo.1984.29.6.1335
|View full text |Cite
|
Sign up to set email alerts
|

Predation on jellyfish and their associates by seabirds

Abstract: Abstract-Scyphozoan jellyfish are preyed on by 11 species of birds in the Bering Sea: Fulmarus glacialis, Pufinus griseus, Pujinus tenuirostris, Oceanodroma furcata, Laws hyperboreus, Rissa tridactyla, Rissa brevirostris, Uria aalge, Uria lomvia, Cyclorrhynchus psittacula, and Aethia cristatella. Parasitic amphipods on scyphomedusae also contribute to avian diets.Predation by birds on gelatinous zooplankton has been documented anecdotally (Anthony 1895;Foxton 1966;Madin 1974;Murie 1979), but has not been sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 2 publications
1
46
0
1
Order By: Relevance
“…Coyle & Cooney (1993) found that the major component of the net tows from the mid-water acoustic features around the Pribilof Islands was gelatinous zooplankton, particularly large schyphozoans. Typically, Cnidaria are not themselves murre prey, although jellyfish do sometimes occur In murre diets (Harrison 1984). However, young stages of gadid fish are often associated with schyphozoans [Mansueti 1963, Van Hyning & Cooney 1974.…”
Section: Discussionmentioning
confidence: 99%
“…Coyle & Cooney (1993) found that the major component of the net tows from the mid-water acoustic features around the Pribilof Islands was gelatinous zooplankton, particularly large schyphozoans. Typically, Cnidaria are not themselves murre prey, although jellyfish do sometimes occur In murre diets (Harrison 1984). However, young stages of gadid fish are often associated with schyphozoans [Mansueti 1963, Van Hyning & Cooney 1974.…”
Section: Discussionmentioning
confidence: 99%
“…Jellyfishes can reproduce both sexually and asexually, which can further lead to a rapid increase in population size. Other than seabirds (Harrison 1984) and other jellyfishes (Hamner 1983, and present study) consuming smaller individuals, we know of no other abundant predators on these medusae. Some fish predators, including adult pollock, are known to prey on jellyfishes in both the Bering Sea (Geoff Lang, Alaska Fisheries Science Center, pers.…”
Section: Potential Causes Of Jellyfish Increasesmentioning
confidence: 99%
“…In general, least auklets specialize on copepods, particularly Neocalanus plumchrus, when available, and crested auklets specialize on euphausiids, particularly Thysanoessa raschii. In contrast, parakeet auklets are more generalized in their diet and take a variety of larval fishes and zooplankton, including gelatinous zooplankton and their commensals (Harrison 1984(Harrison , 1987 …”
Section: Study Area and Focal Speciesmentioning
confidence: 99%